1992
DOI: 10.1016/0735-1097(92)90131-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized angiographic trial of recombinant tissue-type plasminogen activator (alteplase) in myocardial infarction

Abstract: Clot dissolution with restoration of infarct-related artery blood flow is the likely mechanism for the improved prognosis and mortality reduction seen after thrombolytic therapy of acute myocardial infarction. A pilot study has suggested that 100 mg of recombinant tissue-type plasminogen activator (rt-PA) infused over 90 min may lead to higher patency rates than the current standard of 100 mg over 3 h. In this multicenter, randomized, open label trial, 281 patients with acute myocardial infarction receive 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Higher dose and double-bolus regimens have been associated with unacceptable bleeding rates [8,9]. The accelerated or front-loaded dosing regimen has been shown to have higher early patency rates, similar safety profile [6], and lower incidences of reocclusion as compared with the standard dosing regimen [10]. The GUSTO I study (41,021 patients) tested the accelerated dose regimen combined with intravenous heparin.…”
Section: Alteplasementioning
confidence: 99%
See 1 more Smart Citation
“…Higher dose and double-bolus regimens have been associated with unacceptable bleeding rates [8,9]. The accelerated or front-loaded dosing regimen has been shown to have higher early patency rates, similar safety profile [6], and lower incidences of reocclusion as compared with the standard dosing regimen [10]. The GUSTO I study (41,021 patients) tested the accelerated dose regimen combined with intravenous heparin.…”
Section: Alteplasementioning
confidence: 99%
“…Heparin and aspirin should be given concomitantly to prevent reocclusion. The accelerated dosing regimen has been proven to be the most effective [6]: 15 mg bolus over 1-2 min followed by 0.75 mg/kg IV (Յ 50mg) over 30 min followed by 0.5 mg/kg (Յ 35 mg) over 60 min. Weight adjustment is recommended because of excessive bleeding in lighter weight (Ͻ 60 kg) patients and a trend toward decreased lysis in heavy weight (Ͼ 90 kg) individuals [7].…”
Section: Alteplasementioning
confidence: 99%
“…In patients receiving intravenous thrombolytic therapy for acute myocardial infarction, angiography 90 minutes after the initiation of treatment has demonstrated that effective thrombolysis is achieved less frequently with streptokinase (43% to 64%) 24 36 Recently the use of accelerated intravenous dosing regimens of TPA has produced superior results, with 90-minute patency rates ranging from 82% to 91% (mean, 85%) in five studies of a combined total of more than 500 patients. 33 -3740 Thus, for TPA the thrombolytic efficacy of intra-arterial and intravenous routes may be nearly equal.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefit and widespread application of fibrinolytic therapy in the treatment of STEMI, bleeding complications, including devastating hemorrhagic strokes, present a major limitation of this therapy, beyond the substantial proportion (approximately 20%-30%) of patients with failed reperfusion [108][109][110][111][112] and recurrent ischemia. 98,[113][114][115] Although thrombolytics can restore epicardial coronary artery flow, it does not address the underlying unstable plaque and the exposed thrombogenic material thought to cause recurrent ischemic events.…”
Section: Primary Angioplasty In Womenmentioning
confidence: 99%